2004
DOI: 10.1016/s0002-9440(10)63417-7
|View full text |Cite
|
Sign up to set email alerts
|

Lack of the Growth Factor Midkine Enhances Survival against Cisplatin-Induced Renal Damage

Abstract: Although cisplatin acts directly on proximal tubule epithelial cells and causes cell death, little is known regarding the biological significance of its secondary effects, such as inflammation. The growth factor midkine is highly expressed in the proximal tubule and exerts ambivalent activities as to cisplatin nephrotoxicity, ie, anti-apoptotic and chemotactic ones. Here we report that midkine-deficient mice show a significantly higher survival rate than wild-type mice. The levels of blood urea nitrogen and tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 34 publications
(27 reference statements)
1
45
0
Order By: Relevance
“…It may play a role in recruitment of neutrophils and macrophages into inflamed tissue (23,24), and up-regulation of synthesis of inflammatory mediators (25)(26)(27). Animal studies have revealed that several inflammation-related phenomena were substantially alleviated in midkine-deficient animals (12,25,(28)(29)(30)(31)(32). The mechanisms mentioned above may also operate in the involvement of midkine in the pathogenesis of UC since the accumulation of neutrophiles and monocytes associated with aberrant inflammatory response is essential for development of UC (14).…”
Section: Discussionmentioning
confidence: 99%
“…It may play a role in recruitment of neutrophils and macrophages into inflamed tissue (23,24), and up-regulation of synthesis of inflammatory mediators (25)(26)(27). Animal studies have revealed that several inflammation-related phenomena were substantially alleviated in midkine-deficient animals (12,25,(28)(29)(30)(31)(32). The mechanisms mentioned above may also operate in the involvement of midkine in the pathogenesis of UC since the accumulation of neutrophiles and monocytes associated with aberrant inflammatory response is essential for development of UC (14).…”
Section: Discussionmentioning
confidence: 99%
“…14 Second, Mdk À/À mice exhibit significantly milder phenotypes than Mdk þ / þ mice in models of arterial restenosis, ischemic reperfusioninduced renal damage, cisplatin-induced nephropathy and rheumatoid arthritis. [14][15][16][17] Finally, an MK antisense ODN ameliorates arterial restenosis, ischemic reperfusion-induced renal damage and cisplatin-induced nephropathy. [17][18][19] In addition to these indirect data on the relationship between MK and inflammation-related diseases, MK directly induces macrophage migration.…”
mentioning
confidence: 99%
“…[14][15][16][17] Finally, an MK antisense ODN ameliorates arterial restenosis, ischemic reperfusion-induced renal damage and cisplatin-induced nephropathy. [17][18][19] In addition to these indirect data on the relationship between MK and inflammation-related diseases, MK directly induces macrophage migration. 15 We hypothesized that MK plays roles not only in mesangial pathological changes, but also in the inflammation associated with diabetic nephropathy.…”
mentioning
confidence: 99%
“…MK promotes neurite outgrowth and migration in neuronal cells isolated from the embryonic brain (5-7) and prevents apoptosis (8,9). MK also promotes the migration of inflammatory leukocytes (10) and thereby plays a key role in the etiology of neointima formation (10), renal injury (11,12), rheumatoid arthritis (13), and intraperitoneal adhesion after surgery (14). So far, protein-tyrosine phosphatase (7,15), anaplastic lymphoma kinase (16), low density-lipoprotein receptor-related protein-1 (17), low density lipoprotein receptor-related protein 6 (9), and integrin ␣4␤1 and ␣6␤1 (18) have been identified as MK receptors.…”
mentioning
confidence: 99%